Antibacterial warm-keeping composite fabric and preparation method thereof
Through the combination of nano-silver composite cotton fiber, polyester fiber and down, the problems of poor sweat-absorbing and moisture-permeability and insufficient antibacterial performance of traditional warm fabrics are solved, and the excellent performance of antibacterial warm-proof composite fabrics is achieved, improving the comfort and hygiene of wearing.
Patent Information
- Application Number
- CN202411333174.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-24
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2044-09-24
AI Technical Summary
Traditional warm fabrics are poor in sweat-absorbing and moisture-permeable in cold environments, and are uncomfortable to wear, and cannot meet the antibacterial needs of modern consumers for clothing.
Nanosilver composite cotton fiber and polyester fiber are used as outer fabrics, combined with down as filler, and prepared by combining the broad-spectrum antibacterial activity of nanosilver particles and high fluffy and warmth of down, combined with the lightness and durability of polyester fibers. Antibacterial and warm composite fabrics are produced, and uniform adhesion and stability of nanosilver particles are ensured through specific impregnation and drying processes.
It achieves excellent antibacterial properties, lightness and durability and excellent warmth effect of the fabric, extends the cleaning time of clothes, reduces the generation of odors, and improves the comfort and hygiene of wearing.
Abstract
Description
Technical Field
[0001] The present application relates to the field of thermal insulation fabrics, and more specifically, to an antibacterial thermal insulation composite fabric and a preparation method thereof. Background Art
[0002] Thermal insulation fabrics are mainly used to provide sufficient heat retention in cold environments to maintain a comfortable temperature for the human body. Traditional thermal insulation fabrics rely on heavy fiber structures and high density to achieve a warming effect, but such a design often results in poor sweat absorption and moisture permeability of the fabric, making it uncomfortable to wear.
[0003] In recent years, with the development of material science, a variety of new thermal insulation technologies have emerged, such as far-infrared technology. Far-infrared fiber adds powders containing far-infrared functions (such as ceramic powder, etc.) during the spinning process, so that the fiber can absorb and release far-infrared energy, thereby improving the thermal insulation performance of the fabric. This kind of fabric can not only effectively accumulate the heat emitted by the human body, but also convert the absorbed solar energy into far-infrared radiation, further enhancing the thermal insulation effect.
[0004] With the improvement of living standards and the popularization of health knowledge, people are paying more and more attention to their own health. In daily life, people are aware of the potential threat of bacteria, viruses and other microorganisms to health. Therefore, people begin to pay more attention to the antibacterial properties of clothing and are no longer satisfied with the basic need for warmth. Summary of the invention
[0005] In order to simultaneously meet consumers' dual demands for warmth and antibacterial properties of clothing, the present application provides an antibacterial and warmth-keeping composite fabric and a preparation method thereof.
[0006] The antibacterial thermal insulation composite fabric provided in this application adopts the following technical solution: An antibacterial and warm-keeping composite fabric comprises an outer fabric and a filling material, wherein the outer fabric comprises nano-silver composite cotton fibers and polyester fibers, and the filling material comprises down.
[0007] By adopting the above technical scheme, the introduction of nano-silver composite cotton fiber makes the fabric have excellent antibacterial properties. Nano-silver particles have a broad spectrum of antibacterial activity and can effectively inhibit the growth and reproduction of a variety of bacteria, fungi and viruses. This antibacterial property not only prolongs the cleaning time of clothing, but also reduces the generation of odor, improves the hygiene and wearing comfort of clothing. Down as a filling material, due to its extremely high fluffiness and excellent warmth retention, enables the fabric to provide excellent warmth retention. The air barrier in the down can effectively isolate the cold air from the outside while maintaining body temperature, thereby providing lasting warmth protection in a cold environment. The use of polyester fiber gives the fabric light and durable characteristics. Polyester fiber has high strength and elasticity, so that the fabric can maintain a good shape without adding too much weight, ensuring comfortable wearing. At the same time, the blending of polyester fiber and cotton fiber improves the softness of the fabric and enhances the comfort of close-fitting wear.
[0008] Optionally, the preparation method of the nano silver composite cotton fiber is: The cotton fiber is immersed in a sodium hydroxide solution with a mass fraction of 5-10% for alkali treatment, the alkali-treated fiber is neutralized with an acid solution, and the fiber is repeatedly rinsed with deionized water until it is neutral to obtain activated cotton fiber; The activated cotton fiber is immersed in a dispersion of silver nanoparticles with a silver ion concentration of 100-200ppm, and immersed for 30-60min at a temperature of 50-60°C and a stirring speed of 150-200r / min. After the immersion is completed, the fiber is taken out and slightly squeezed to remove excess liquid.
[0009] The cotton fiber loaded with nano-silver is dried at 40-60° C. to obtain nano-silver composite cotton fiber.
[0010] By adopting the above technical scheme, the cotton fiber is immersed in a 5-10% sodium hydroxide solution for alkali treatment, the purpose of which is to remove impurities and wax layers on the surface of the cotton fiber and increase the active sites on the fiber surface. This treatment step makes the surface of the cotton fiber more hydrophilic, which is conducive to the subsequent adsorption of silver nanoparticles. The fiber treated with alkali is neutralized with acid and repeatedly rinsed with deionized water to ensure that the fiber reaches a neutral state. This step is to prevent residual alkaline substances from damaging the fiber and ensure the smooth progress of subsequent treatment. The activated cotton fiber is immersed in a dispersion of silver nanoparticles, and the silver ion concentration is controlled at 100-200ppm. The silver nanoparticles are uniformly adsorbed on the surface of the cotton fiber by impregnation treatment at a temperature of 50-60°C and stirring conditions of 150-200r / min. Appropriate temperature and stirring rate ensure the effective dispersion of silver nanoparticles and form a stable attachment layer on the surface of the cotton fiber. This uniform loading method ensures the antibacterial effect of nanosilver without affecting the softness and other physical properties of the fiber. The impregnated cotton fiber is dried at 40-60°C. The lower drying temperature can avoid the loss or aggregation of nanosilver particles while maintaining the softness of cotton fibers. The nanosilver composite cotton fibers obtained in this process have good antibacterial properties and retain the original comfort of cotton fibers.
[0011] Optionally, thioglycolic acid needs to be added to the dispersion, and the added amount of the thioglycolic acid is 0.1-0.17 g / L.
[0012] By adopting the above technical solution, thioglycolic acid has a -SH group, which can chemically bond with the surface of silver nanoparticles to form a stable silver-sulfur bond. This effect effectively prevents the aggregation of silver nanoparticles in the solution, keeps them highly dispersible, and ensures that the silver nanoparticles are evenly attached to the surface of cotton fibers. Thioglycolic acid can not only stabilize silver nanoparticles, but also regulate the release rate of silver ions. Adding an appropriate amount of thioglycolic acid (0.1-0.17g / L) can ensure that nanosilver has a sustained antibacterial effect and can still exert its antibacterial function after long-term wearing or multiple washings. Due to the addition of thioglycolic acid, the silver nanoparticles are more evenly distributed on the fiber surface, effectively increasing the surface active area of the fiber. In this way, the antibacterial effect is further improved, and the growth of bacteria can be more effectively inhibited.
[0013] Optionally, the outer fabric also includes bamboo charcoal fiber.
[0014] By adopting the above technical scheme, bamboo charcoal fiber is made of bamboo charcoal and has natural antibacterial properties. Bamboo charcoal contains rich porous structures, which can absorb harmful substances and odors in the air, and inhibit the growth of bacteria and mold through its internal mineral components. The combination with nano-silver composite cotton fiber enhances the overall antibacterial properties of the fabric. Bamboo charcoal fiber has good moisture absorption and perspiration ability, keeping the skin dry. This is very important for warm clothing that needs to be worn for a long time, which can improve comfort.
[0015] Optionally, the filling material also includes artificial down.
[0016] Optionally, the mass ratio of the down to artificial down is 5:(2-4).
[0017] By adopting the above technical solution, down is a natural thermal insulation material, and its fiber is thin and long, which can lock a large amount of air and form a good thermal insulation layer. Down has high fluffiness and can rebound quickly to maintain the volume and softness of clothing. This makes the fabric not only warm, but also very comfortable to wear. Artificial down has good durability and water resistance. Compared with natural down, artificial down can better maintain its thermal insulation performance in a humid environment, is not easy to get heavy due to moisture, and is not easy to clump. In addition, artificial down is treated with antibacterial agents to prevent bacteria from growing and improve hygiene. Down and artificial down are mixed in a mass ratio of 5: (2-4), so that the fabric retains the excellent thermal insulation of down while increasing the durability and water resistance of artificial down. This combination ensures that the fabric is both light and has a good thermal insulation effect, and is not easy to get damp and clump. The addition of artificial down can enhance the structural stability of the fabric, reduce the movement and deformation of the filler inside the fabric, thereby improving the durability of the clothing and the durability of the thermal insulation performance.
[0018] In a second aspect, the present application provides a method for preparing an antibacterial thermal insulation composite fabric, which adopts the following technical scheme: A method for preparing an antibacterial thermal insulation composite fabric, comprising the following steps: 70-75% of nano-silver composite cotton fibers and 25-30% of polyester fibers are mixed and spun to obtain blended yarns, and the blended yarns are made into outer fabrics through a weaving machine. After weaving, the outer fabrics are heat-set; The outer fabric is laid flat, the filling material is evenly distributed on the outer fabric, and then another layer of the outer fabric is laid flat on the surface of the filling material, and laminated by hot pressing to obtain the antibacterial and thermal insulation composite fabric.
[0019] By adopting the above technical scheme, the fabric is endowed with good antibacterial properties by blending 70-75% nano-silver composite cotton fiber with 25-30% polyester fiber. During the preparation process, the blended yarn is woven into the outer fabric, and the filling material (down and artificial down) is added between the two layers of outer fabric to form a good thermal insulation layer. The fluffiness of down combined with the water resistance of artificial down not only improves the thermal insulation performance, but also ensures the lightness and softness of the fabric. After the outer fabric is heat-set, the structure of the fabric is more stable and not easy to deform, which improves the durability and windproof performance of the fabric. At the same time, the heat-setting process makes the fabric more elastic and increases comfort. The filling material is evenly distributed between the two layers of outer fabric and laminated by hot pressing, so that the layers of the fabric are firmly combined to form a tight composite structure. This process ensures that the fabric has good structural stability, the filling material will not move or clump, and further improves the durability and warmth of the garment.
[0020] Optionally, the filler needs to be processed as follows before use: The filling material is immersed in a 30% mass concentration organosilicon quaternary ammonium salt solution for 10-30 minutes. The soaked down is initially passed through a spin-drying device to remove excess solution to prevent the down from being overly wet. The down is dried at 40-60°C until the down is completely dry, and the filling material is loosened again through a loosening device.
[0021] By adopting the above technical solution, organosilicon quaternary ammonium salt can effectively inhibit the growth of various bacteria and fungi. The filler (down or artificial down) is immersed in this solution for 10-30 minutes to evenly cover the fiber surface with the antibacterial agent, thereby giving the filler a lasting antibacterial property. This treatment step is essential to improving the overall hygienic performance of the fabric, especially in high humidity or high sweat environment, which can effectively prevent the growth of microorganisms. Drying the filler at a temperature range of 40-60°C can effectively remove moisture from the filler while maintaining the fluffiness and softness of the down, thereby ensuring the warmth-keeping effect of the filler. After the filler is dried, it is loosened again by a loosening device. This step is to restore the fluffiness of the filler and avoid the bonding or agglomeration of the fibers during the impregnation and drying process. The loosening treatment makes the distribution of the filler more uniform, which helps to better play a warming role in the filling process in the fabric.
[0022] In summary, this application has the following beneficial effects: 1. The present invention combines nano-silver composite cotton fiber and polyester fiber to give the fabric excellent antibacterial properties and light durability. Nano-silver particles provide broad-spectrum antibacterial protection, effectively inhibit the growth of bacteria, fungi and viruses, extend the cleaning time of clothing and reduce odor. Down as a filling material, with its high fluffiness and excellent warmth retention, provides continuous warmth in cold environments. Polyester fiber enhances the strength and elasticity of the fabric, ensures comfortable wearing and stable shape, and makes the fabric have excellent warmth retention, antibacterial and comfort properties.
[0023] 2. In the present application, it is preferred to treat the cotton fiber with alkali to remove impurities and waxy layers, and then uniformly adsorb the silver nanoparticles, and combine with the addition of thioglycolic acid to form a stable adhesion layer on the fiber surface. The addition of thioglycolic acid prevents the aggregation of silver nanoparticles and regulates the release rate of silver ions, thereby ensuring the continuous antibacterial performance of the fiber. This treatment step not only improves the antibacterial effect of the nano-silver composite cotton fiber, but also retains the softness and comfort of the fiber, and can effectively inhibit bacterial growth even after long-term wearing or multiple washings.
[0024] 3. The method of the present application is made by blending 70-75% nano-silver composite cotton fiber with 25-30% polyester fiber, weaving it into an outer layer fabric, and filling it with down and artificial down, and then making it through a hot pressing lamination process. The nano-silver composite cotton fiber gives the fabric excellent antibacterial properties, while the combination of down and artificial down provides excellent warmth retention and lightness. The heat setting treatment improves the structural stability, wind resistance and durability of the fabric, ensures the firm combination of each layer of material, and enhances the warmth retention effect and overall comfort of the fabric. DETAILED DESCRIPTION
[0025] The present application is further described in detail below in conjunction with the examples. It is particularly noted that if no specific conditions are specified in the following examples, the experiments are carried out according to conventional conditions or the conditions recommended by the manufacturer. Unless otherwise specified, the raw materials used in the following examples can be obtained from common commercial sources.
[0026] Preparation example of nano silver composite cotton fiber Preparation Example 1 Preparation method of nano silver composite cotton fiber: 20 kg of cotton fiber was soaked in a sodium hydroxide solution with a mass fraction of 8% for alkali treatment for 10 minutes, the alkali-treated fiber was neutralized with citric acid, and the fiber was repeatedly rinsed with deionized water until it was neutralized to obtain activated cotton fiber; The activated cotton fibers were immersed in a dispersion of silver nanoparticles with a silver ion concentration of 150 ppm at 55°C and 180 r / min stirring for 45 min. After the immersion was completed, the fibers were taken out and gently squeezed to remove excess liquid.
[0027] The cotton fiber loaded with nanosilver was dried at 50°C to obtain nanosilver composite cotton fiber.
[0028] Preparation Example 2 Preparation method of nano silver composite cotton fiber: 20 kg of cotton fiber was soaked in a sodium hydroxide solution with a mass fraction of 8% for alkali treatment for 10 minutes, the alkali-treated fiber was neutralized with citric acid, and the fiber was repeatedly rinsed with deionized water until it was neutralized to obtain activated cotton fiber; The activated cotton fiber was immersed in a dispersion of silver nanoparticles with a silver ion concentration of 150ppm, and then thioglycolic acid was added with a concentration of 0.14g / L. The fiber was immersed for 45 minutes at 55°C and 180r / min stirring. After the immersion was completed, the fiber was taken out and gently squeezed to remove excess liquid.
[0029] The cotton fiber loaded with nanosilver was dried at 50°C to obtain nanosilver composite cotton fiber.
[0030] Preparation Example 3 Preparation method of nano-silver composite cotton fiber: The difference from Preparation Example 2 is that the concentration of thioglycolic acid is 0.07 g / L.
[0031] Preparation Example 4 Preparation method of nano-silver composite cotton fiber: The difference from Preparation Example 2 is that the concentration of thioglycolic acid is 0.2 g / L. Example
[0032] Example 1 A method for preparing an antibacterial thermal insulation composite fabric: 7.5 kg of nano silver composite cotton fiber and 2.5 kg of polyester fiber were prepared. The nano silver composite cotton fiber was obtained by the process of Preparation Example 1, and the nano silver composite cotton fiber and the polyester fiber were spun by a blending machine to obtain a 50D blended yarn; The prepared blended yarn is woven into an outer fabric by a flat weaving method on a braiding machine. After the weaving is completed, the outer fabric is subjected to a heat setting treatment at 150°C for 60 seconds. Lay the outer fabric after heat setting on the workbench to ensure that the surface is flat and without creases. Use duck down as the filling material, and evenly distribute the duck down on the laid outer fabric with a thickness of 5mm. Lay another layer of outer fabric on the filling material, and laminate the two layers of outer fabric and the filling material in the middle by hot pressing, with a temperature of 140℃, a pressure of 3MPa, and a processing time of 90s.
[0033] Example 2 A method for preparing an antibacterial and thermal insulation composite fabric: The method is different from Example 1 in that 7 kg of nano-silver composite cotton fiber, 2 kg of polyester fiber and 1 kg of bamboo charcoal fiber are prepared for blending to obtain a 50D blended yarn.
[0034] Example 3 A method for preparing an antibacterial and thermal insulation composite fabric: The method is different from Example 1 in that the filling material is a mixture of duck down and artificial down in a mass ratio of 5:2.
[0035] Example 4 A method for preparing an antibacterial and thermal insulation composite fabric: The method is different from Example 1 in that the filling material is a mixture of duck down and artificial down in a mass ratio of 5:3.
[0036] Example 5 A method for preparing an antibacterial and thermal insulation composite fabric: The method is different from Example 1 in that the filling material is a mixture of duck down and artificial down in a mass ratio of 5:4.
[0037] Example 6 A method for preparing an antibacterial and thermal insulation composite fabric: The method is different from Example 1 in that the nano-silver composite cotton fiber is obtained through the process of Preparation Example 2.
[0038] Example 7 A method for preparing an antibacterial and thermal insulation composite fabric: The difference from Example 1 is that the filling material is immersed in a 30% mass concentration organosilicon quaternary ammonium salt solution for 20 minutes before use, the immersed down is passed through a drying device to initially remove excess solution to prevent the down from being excessively wet, the down is dried at 50°C until the down is completely dry, and the filling material is loosened again through a loosening device.
[0039] Comparative Example Comparative Example 1 A method for preparing an antibacterial thermal insulation composite fabric: 7.5 kg of cotton fiber and 2.5 kg of polyester fiber were prepared. The nano-silver composite cotton fiber was obtained by the process of Preparation Example 1, and the nano-silver composite cotton fiber and the polyester fiber were spun through a blending machine to obtain a 50D blended yarn; The prepared blended yarn is woven into an outer fabric by a flat weaving method on a braiding machine. After the weaving is completed, the outer fabric is subjected to a heat setting treatment at 150°C for 60 seconds. Lay the outer fabric after heat setting on the workbench to ensure that the surface is flat and without creases. Use duck down as the filling material, and evenly distribute the duck down on the laid outer fabric with a thickness of 5mm. Lay another layer of outer fabric on the filling material, and laminate the two layers of outer fabric and the filling material in the middle by hot pressing, with a temperature of 140℃, a pressure of 3MPa, and a processing time of 90s.
[0040] Comparative Example 2 A method for preparing an antibacterial and thermal insulation composite fabric: The difference from Example 6 is that the nano-silver composite cotton fiber is obtained through the process of Preparation Example 3.
[0041] Comparative Example 3 A method for preparing an antibacterial and thermal insulation composite fabric: The difference from Example 6 is that the nano-silver composite cotton fiber is obtained through the process of Preparation Example 4.
[0042] Performance testing Detection Methods Thermal insulation test Heat the sample to 60°C, remove the heating source, and record the temperature change of the sample over a period of time. Calculate the thermal insulation rate of the sample, that is, the percentage of the sample temperature drop after a period of time. The higher the thermal insulation rate, the better the thermal insulation performance of the fabric.
[0043] Antimicrobial testing According to the ISO 20743 standard, the E. coli suspension was inoculated onto the fabric sample. After the sample was cultured at 37°C for 24 hours, the number of colonies on the sample was measured and compared with the control sample to calculate the antibacterial activity value. The larger the antibacterial activity value, the better the antibacterial effect of the fabric.
[0044] Table 1 Test data Insulation rate / % Antimicrobial activity value Example 1 61.5 >3 Example 2 61.3 >3 Example 3 64.0 >3 Example 4 63.8 >3 Example 5 63.4 >3 Example 6 64.2 >3 Example 7 64.3 >3 Comparative Example 1 60.3 <2 Comparative Example 2 60.5 >3 Comparative Example 3 58.6 2-3 Combining Example 1 and Comparative Example 1 with Table 1, it can be seen that the introduction of nano-silver composite cotton fibers enables the fabric to have excellent antibacterial properties. Nano-silver particles have a broad spectrum of antibacterial activity and can effectively inhibit the growth and reproduction of a variety of bacteria, fungi and viruses.
[0045] Combining Example 6 and Comparative Example 2-3 with Table 1, it can be seen that adding an appropriate amount of thioglycolic acid (0.1-0.17 g / L) can ensure that the nanosilver has a sustained antibacterial effect and can still play an antibacterial function after long-term wearing or multiple washings. Too low an effect is not obvious, and too high an effect will affect the composite effect of nanosilver.
[0046] It can be seen from the embodiment 1-6 and in combination with Table 1 that the bamboo charcoal fiber is made of bamboo charcoal and has natural antibacterial properties. Bamboo charcoal contains abundant porous structures, can absorb harmful substances and peculiar smell in the air, and inhibits the growth of bacteria and molds through its internal mineral components. The combination with nano silver composite cotton fiber enhances the overall antibacterial properties of the fabric. Down and artificial down are mixed according to the mass ratio of 5: (2-4), so that the fabric increases the durability and water resistance of artificial down while retaining the excellent warmth retention of down. Organosilicon quaternary ammonium salt can effectively inhibit the growth of various bacteria and fungi. The filler is immersed in this solution for 10-30 minutes, so that the antibacterial agent is evenly covered on the fiber surface, thereby giving the filler a lasting antibacterial property.
[0047] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. An antibacterial thermal insulation composite fabric, characterized in that: It comprises an outer layer fabric and a filling material, wherein the outer layer fabric comprises nano-silver composite cotton fiber and polyester fiber, and the filling material comprises down.
2. The antibacterial thermal insulation composite fabric according to claim 1, characterized in that: The preparation method of the nano silver composite cotton fiber is: The cotton fiber is immersed in a sodium hydroxide solution with a mass fraction of 5-10% for alkali treatment, the alkali-treated fiber is neutralized with an acid solution, and the fiber is repeatedly rinsed with deionized water until it is neutral to obtain activated cotton fiber; The activated cotton fiber is immersed in a dispersion of silver nanoparticles with a silver ion concentration of 100-200ppm, and immersed for 30-60min at a temperature of 50-60°C and a stirring speed of 150-200r / min. After the immersion is completed, the fiber is taken out and slightly squeezed to remove excess liquid.
3. Dry the cotton fiber loaded with nanosilver at 40-60°C to obtain nanosilver composite cotton fiber.
4. The antibacterial thermal insulation composite fabric according to claim 1, characterized in that: Thioglycolic acid needs to be added to the dispersion, and the added amount of the thioglycolic acid is 0.1-0.17 g / L.
5. The antibacterial thermal insulation composite fabric according to claim 1, characterized in that: The outer fabric also includes bamboo charcoal fibers.
6. The antibacterial thermal insulation composite fabric according to claim 1, characterized in that: The filling material also includes artificial down.
7. The antibacterial thermal insulation composite fabric according to claim 5, characterized in that: The mass ratio of the down to the artificial down is 5:(2-4).
8. A method for preparing the antibacterial thermal insulation composite fabric according to any one of claims 1 to 6, characterized in that: The following steps are involved: 70-75% of nano-silver composite cotton fibers and 25-30% of polyester fibers are mixed and spun to obtain blended yarns, and the blended yarns are made into outer fabrics through a weaving machine. After weaving, the outer fabrics are heat-set; The outer fabric is laid flat, the filling material is evenly distributed on the outer fabric, and then another layer of the outer fabric is laid flat on the surface of the filling material, and laminated by hot pressing to obtain the antibacterial and thermal insulation composite fabric.
9. The method for preparing the antibacterial thermal insulation composite fabric according to claim 7, characterized in that: The filler also needs to be processed as follows before use: Immerse the filling material in a 30% mass concentration organosilicon quaternary ammonium salt solution for 10-30 minutes, pass the immersed down through a spin-drying device to initially remove excess solution to avoid excessive moisture in the down, dry the down at 40-60°C until the down is completely dry, and loosen the filling material again through a loosening device.
Citation Information
Patent Citations
Antibacterial warp-knitted lace fabric and preparation method thereof
CN113862991A
Down jacket with high thermal insulation performance and preparation method thereof
CN114766753A
Heat preservation base cloth fabric compounded with down fabric
CN118181884A
Antibacterial polyester fiber based on silver-containing zirconium phosphate, and method for preparation thereof
WO2017092233A1
Fibroin nano-silver antibacterial color-developing finishing agent, preparation method therefor, and application thereof
WO2023279956A1
Cited By
Preparation method of damp-proof and antibacterial medicine packaging composite material with multiple barrier functions
CN120439635A